Evaluasi Program Pemberdayaan Lembaga Kemasyaratan dalam Peningkatan Teknologi Tepat Guna pada Dinas Pemberdayaan Masyarakat dan Desa Kabupaten Malinau, Provinsi Kalimantan Utara - Kiring Yopi; Muhlis Hafel; Darmanto (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
The purpose of this study is to analyze and identify community empowerment programs in improving appropriate technology at the Malinau Regency Community and Village Empowerment Office using the CIPP (Context, Input, Process, and Product) method. The method used uses a qualitative method with a survey design and in-depth interviews. Data was collected through interviews with resource persons of the head of the office, secretary, head of the field, staff of the empowerment office and the community. The results of data analysis show that the CIPP evaluation of the community empowerment program through appropriate technology in Malinau Regency shows effectiveness in increasing community independence and productivity despite various challenges. The input evaluation indicates the need for transparent management of funds and resources, active participation, and the use of technology that is appropriate to local conditions. In terms of process, program implementation adhered to SOPs, increased community safety and satisfaction, and training was effective in enhancing skills. The product evaluation showed that the program succeeded in increasing the capacity and independence of the institution and had a positive impact on community welfare. Challenges include limited access to technology, resources, and lack of training and collaboration, but enabling factors such as government support, planning, and distribution of tools remain key strengths in implementation.